Implementasi Kebijakan Kedisiplinan Peserta Didik Di SMK Negeri 1 Maumere - Mite Albertus; Akhsanul In’am (Jurnal Kebijakan dan Pengembangan Pendidikan, 2017)
Abstract: This study aims to describe the implementation of disciplinary policies of students in SMK Negeri 1 Maumere; 2) what obstacles are faced by SMK Negeri 1 Maumere in implementing disciplinary policies; 3) what efforts have been made to overcome problems or obstacles in the implementation of discipline. The research method used is a qualitative descriptive research method. to be informants in this study are 1) Tatib Team Coordinator, 2) BK Teachers. Data collection in this study uses the following methods: 1) interview 2) Observation, 3) Documentation. This study uses the analysis method and the Moles and Huberman (1994) model with the stages of data reduction, presenting data, and drawing conclusions. Testing the data in this study uses a participation extension technique which means a single researcher in the field until the saturation of data collection is achieved. The results of this study indicate (1) The implementation of student disciplinary policies at SMK Negeri 1 Maumere meets the standards that have been formulated by the Tatib team. (2) The obstacles that become obstacles in the implementation of disciplinary policies of students in SMK Negeri 1 Maumere are 1) from the students, 2) lack of support from parents, 3) from the school which consists of administration that has not been neatly arranged and lack of support from the teacher.Keywords: Policy implementation, Discipline, Students Abstrak: Penelitian ini bertujuan untuk mendeskripsikan implementasi kebijakan kedisiplinan peserta didik di SMK Negeri 1 Maumere; 2) kendala apa saja yang dihadapi SMK Negeri 1 Maumere dalam melaksanakan kebijakan kedisiplinan; 3) upaya-upaya apa saja yang sudah dilakukan untuk mengatasi masalah atau kendala dalam pelaksanaan kedisiplinan. Metode penelitian yang digunakan adalah metode penelitian deskritif kualitatif. menjadi imforman dalam penelitian ini adalah 1) Koordinator Tim Tatib, 2) Guru BK. Pengumpulan data dalam penelitian ini menggunakan metode 1) wawancara 2) Observasi, 3) Dokumentasi. Penelitian ini menggunakan metode analisis dan model Moles and Huberman (1994) dengan tahapan reduksi data, menyajikan data, dan penarikan kesimpulan. Pengujian data dalam penelitian ini menggunakan teknik perpanjangan keikutsertaan yang berarti peneliti tunggal di lapangan sampai kejenuhan pengumpulan data tercapai. Hasil penelitian ini menunjukkan (1) Implementasi kebijakan kedisiplinan peserta didik di SMK Negeri 1 Maumere pada dasarnya sudah memenuhi standar yang telah dirumuskan oleh tim tatib. (2) Kendala-kendala yang menjadi hambatan dalam pelaksanaan kebijakan kedisiplinan peserta didik di SMK Negeri 1 Maumere adalah 1) dari pihak peserta didik, 2) kurang adanya dukungan dari orangtua, 3) dari pihak sekolah yang terdiri dari administrasi yang belum tertata rapi dan kurang adanya dukungan dari guru.Kata kunci: Implementasi kebijakan, Kedisiplinan, Peserta didik